Bone density in asthmatic patients taking high dose inhaled beclomethasone dipropionate and intermittent systemic corticosteroids. Issue 6 (June 1992) - Packe, G E; Douglas, J G; McDonald, A F; Robins, S P; Reid, D M
Abstract : BACKGROUND: Asthmatic patients taking low to moderate doses of inhaled topical corticosteroids have been shown to have lower bone density than those taking bronchodilators only. There is little information on bone density in asthmatic patients taking high dose inhaled corticosteroids. METHODS: Bone mass was studied in three age matched groups of asthmatic patients. These comprised: 17 asthmatic patients who had never taken inhaled or systemic corticosteroids (group 1); 20 patients who had taken beclomethasone diproprionate in a dosage of 1000-2000 micrograms daily for at least a year, who had also received courses of systemic corticosteroids in the past (group 2); and 20 patients who were taking both high dose inhaled corticosteroids and regular low dose prednisolone, at a median dose of 7 mg daily (group 3). Vertebral bone density was measured by quantitative computed tomography. Biochemical indices of bone formation and resorption were also measured. RESULTS: Mean bone density in group 2 (127.5(22.6) mg/ml) was similar to that in group 3 (114.5 (36.0) mg/ml). Bone density was significantly lower in both of these groups than in group 1 (160.4 (27.4) mg/ml). There were no significant differences between groups for any of the markers of bone formation and resorption. CONCLUSIONS: Asthmatic patients receiving high dose inhaled beclomethasone and intermittent courses of systemic corticosteroids have reduced vertebral bone density. The bone loss is similar in degree to that seen in patients taking high dose inhaled topical corticosteroids and continuous low dose systemic corticosteroids.